PROTOTYPE ALAT PERATAAN DAN PEMADATAN TANAH BERBASIS Internet of Things (IoT) - Amin, Muchammad Fahrul Amin; Wahyu Dirgantara; Yandhika Surya Akbar Gumilang (JURNAL QUANCOM: QUANTUM COMPUTER JURNAL, 2024)
ped with ESP32-Cam, DC Motor, and BTS 7960 Motor Driver, and will be operated remotely via a smartphone's Android remote control, utilizing IoT technology to enhance efficiency and accuracy in soil leveling and compaction. By three trials result on sandy soil showed a more significant reduction, with an averagThe purpose of this research is to design a prototype of a soil leveling and compaction tool based on the Internet of Things (IoT). Currently, many projects still rely on manual tools for soil leveling and compaction, which can result in reduced effectiveness, lack of safety for workers, and high levels of fatigue. Therefore, this tool is equipe of 3.6 mm in 4 seconds, compared to rocky soil, which had an average reduction of 3.3 mm in 5.3 seconds over three trials.